2021
DOI: 10.1016/s2352-3026(21)00060-0
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in patients treated with chimeric antigen receptor T-cell therapy who were admitted to intensive care (CARTTAS): an international, multicentre, observational cohort study

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 28 publications
3
44
2
2
Order By: Relevance
“…CAR-T-терапия позволяет добиться успеха в случаях, когда химиотерапия оказывается безуспешной, однако у 47% больных развиваются угрожающие жизни осложнения [12]. Ранняя летальность в ОРИТ у перенесших CAR-T-терапию составляет 6%, 90-дневная летальность -22,5% [13]. До 27% больных после CAR-T-терапии вследствие СВЦ нуждаются в вазопрессорной терапии [13], 44% -в оксигенотерапии, 13% -в искусственной вентиляции легких (ИВЛ) [2].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…CAR-T-терапия позволяет добиться успеха в случаях, когда химиотерапия оказывается безуспешной, однако у 47% больных развиваются угрожающие жизни осложнения [12]. Ранняя летальность в ОРИТ у перенесших CAR-T-терапию составляет 6%, 90-дневная летальность -22,5% [13]. До 27% больных после CAR-T-терапии вследствие СВЦ нуждаются в вазопрессорной терапии [13], 44% -в оксигенотерапии, 13% -в искусственной вентиляции легких (ИВЛ) [2].…”
Section: Discussionunclassified
“…Ранняя летальность в ОРИТ у перенесших CAR-T-терапию составляет 6%, 90-дневная летальность -22,5% [13]. До 27% больных после CAR-T-терапии вследствие СВЦ нуждаются в вазопрессорной терапии [13], 44% -в оксигенотерапии, 13% -в искусственной вентиляции легких (ИВЛ) [2]. Риск развития СВЦ зависит от объема опухоли, типа клеточного продукта, поскольку конструкция химерных клеток и технология их производства влияют на способность клеток к пролиферации и на их активность, а также дозы химерных клеток, предшествующей лимфодеплетирующей химиотерапии, сопутствующей патологии [14].…”
Section: Discussionunclassified
“…Due to the similarity of symptoms and the immunosuppressed state of the patient it is crucial to exclude sepsis and treat infections appropriately. In a recent study on outcomes in critically ill CAR T recipients, sepsis was one of the main reasons for ICU admission [ 34 ]. Sepsis-related encephalopathy and meningitis/encephalitis can mimic ICANS.…”
Section: Key Toxicities Related To Car T-therapymentioning
confidence: 99%
“…In this survey, reasons for admitting lower grade toxicities were concerns for later deterioration, need for further interventions, concerns for evolving noncardiogenic pulmonary edema, or risk for rapid deterioration due to large tumor burden [ 10 ]. The CARTTAS trial investigating outcomes in patients treated with CAR‑T cells revealed that about 30% of the patients required admission to ICU, all for CRS, ICANS, or sepsis [ 34 ].…”
Section: Management Of Car T-cell-related Toxicitiesmentioning
confidence: 99%
See 1 more Smart Citation